ذكر التهذيب والتأديب في الكلام المنظوم والمنثور من خزانة الأدب وغاية الأرب للحموي (دراسة وصفية تطبيقية): An Analytical study of Rectification and Discipline: Poetry and Prose in Khizānat al-Adab va Ghayato al-arib of Al-Ḥamavī - Mr. Abdullah; Prof. Dr. Naseeb Dar Muhammad (Late) (Al Manhal Research Journal, 2023)
Ilm al-Badī (Embellishments) is one of the three important sciences of Arabic Rhetoric, which sub divided into: Al Muhāsanāt Al- Lafziyyah (Lexical Embellishments), Al Muhāsanāt Al-Ma‘nawīyyah (semantical Embellishments). Among the most important topics of Lexical Embellishments is Zikr altahzeeb wa tadeeb Rectification and Discipline which related to text of literature e.g poetry & prose..Some rhetoric’s scholars cited this topic with examples in their books, one of these is Ibn Ḥijjah al-Ḥamavī, Abū Bakr ibn ‘Alī (died: 837AH). His famouse book is Khizānat al-Adab wa-ghāyat Al-Arab. In this book he cited many topics of ‘Ilm al-Badī‘(Embellishments), and especially Zikr altahzeeb wa tadeeb along with examples from poetry of different poets and prose with several kinds. The Ḥamavī has focused on this correctly and the Arabic rhetoric scholars quoted the excellent beginning researchers tried their best to collect some relevant examples of this topic to prove that All of them worked in their text.